2012
DOI: 10.1007/s10964-012-9748-9
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Daughters’ Romantic Competence: The Role of Divorce, Quality of Parenting, and Maternal Romantic History

Abstract: This study examined the links between parental divorce, quality of maternal parenting, spousal relationships and middle adolescent romantic competence in 80 mother-adolescent daughter pairs (40 divorced). Mothers were asked to describe their attitudes and behaviors with regard to their daughters' romantic behavior. In addition, mothers were interviewed about their own romantic experiences when they were at the age of their daughters. Adolescent girls (mean age = 16.98 years; range 16-18) were administered a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 57 publications
1
11
0
4
Order By: Relevance
“…This study provides evidence that the stress of IPC and PI may lead to a multitude of adjustment difficulties in sequence. To our knowledge, no previous studies have examined whether both PI and romantic competence mediate the association between IPC and internalizing psychopathology in emerging adulthood, despite arguments that both of these variables are implicated as consequences of IPC (e.g., Coln, Jordan, & Mercer, ; Erel & Burman, ; McElwain & Volling, ; Shulman et al, ; Steinberg & Davila, ) and that the quality of family relationships is critical for emerging adulthood functioning (Larose & Boivin, ). Our model now supports the notion that IPC and parental intrusion interfere with emerging adults' competence in romantic relationships and that romantic competence contributes as a proximal predictor of symptoms of depression and loneliness in college.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides evidence that the stress of IPC and PI may lead to a multitude of adjustment difficulties in sequence. To our knowledge, no previous studies have examined whether both PI and romantic competence mediate the association between IPC and internalizing psychopathology in emerging adulthood, despite arguments that both of these variables are implicated as consequences of IPC (e.g., Coln, Jordan, & Mercer, ; Erel & Burman, ; McElwain & Volling, ; Shulman et al, ; Steinberg & Davila, ) and that the quality of family relationships is critical for emerging adulthood functioning (Larose & Boivin, ). Our model now supports the notion that IPC and parental intrusion interfere with emerging adults' competence in romantic relationships and that romantic competence contributes as a proximal predictor of symptoms of depression and loneliness in college.…”
Section: Discussionmentioning
confidence: 99%
“…Además, un elevado nivel de conflicto parental puede transmitirse como un modelo negativo para el manejo de las relaciones, desarrollando peores habilidades de enfrentamiento a los conflictos de pareja 28 . Una mayor exposición al conflicto parental en la niñez, se asocia, en la adolescencia y adultez, con parejas que terminan su relación más rápido, tienen relaciones insatisfactorias y mayor violencia dentro de la pareja 22,[29][30][31] .…”
Section: Consecuencias a Largo Plazo En El Plano Afectivo De La Discounclassified
“…El conflicto parental tiene mayor impacto en las conductas sexuales de riesgo en los hijos que el divorcio de los padres 32 . Se ha observado que las hijas adolescentes tienen una visión menos positiva de las relaciones amorosas, menos probabilidades de involucrarse en ellas, y si lo hacen, son menos estables 28 . Wallerstein y Corbin encontraron que una relación padre-hija deficiente se asoció con un ajuste social deficiente en las hijas (hasta diez años postseparación) y que durante la adolescencia estas niñas tenían mayor probabilidad de una actividad sexual precoz y promiscua 33 .…”
Section: Consecuencias a Largo Plazo En El Plano Afectivo De La Discounclassified
See 1 more Smart Citation
“…For example, in a longitudinal study following participants from birth to emerging adulthood, Roisman, Collins, Sroufe, and Egeland () found that individuals classified as securely attached during infancy had higher quality romantic relationships in emerging adulthood as compared to their counterparts. Additionally, studies with 15‐ 17‐year‐old adolescents have shown that parental warmth, sensitivity, and supportiveness are associated with greater intimacy, romantic relationship satisfaction, and more mature attitudes toward romantic relationships during emerging adulthood (Auslander, Short, Succop, & Rosenthal, ; Conger et al, ; Dalton, Frick‐Horbury, & Kitzmann, ; Dinero, Conger, Shaver, Widaman, & Larsen‐Rife, ; Roisman, Booth‐LaForce, Cauffman, & Spieker, ; Shulman, Zlotnik, Shachar‐Shapira, Connolly, & Bohr, ). The study by Conger and colleagues () is particularly compelling as it involved a prospective, longitudinal design, in which parent–adolescent interactions were observed repeatedly when the adolescent was 14–17 years old, and romantic relationship behaviors were observed when the target participant was 20 years old.…”
mentioning
confidence: 99%